Investigating Factors Influencing Treatment Outcomes of Pulmonary Tuberculosis: A Cross-Sectional Study Based on Community Health Center Registry in Surakarta - Bragastio, Muhamad Rico Aldrian Renandri; Suyatmi, Suyatmi; Raharjo, Ahmad Farih; Aphridasari, Jatu (Smart Medical Journal, 2024)
Introduction: Pulmonary tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis. The successful treatment of pulmonary TB can be influenced by several factors, namely gender, age, body mass index (BMI), and comorbid diseases. This study aims to investigate whether those factors influence the treatment outcome of pulmonary TB patients in Surakarta.Method: This study is an analytical observational study with a cross-sectional design. The research subjects were pulmonary tuberculosis patients treated in 2020-2022 at Ngoresan, Setabelan, and Sibela Community Health Center of Surakarta. The inclusion criteria was pulmonary TB patient over 15 years old. Patients suffering from other pulmonary diseases or with incomplete medical record were excluded.Results: This study involved 101 subjects. Multivariate analysis was conducted using the logistic regression test and bivariate analysis showed that there were not any significant effect of age, BMI, and comorbid diseases observed on treatment outcome with p=0.571, p=0.147, and p=0.13 respectively. Interestingly, gender was found to be significantly influencing the outcome of pulmonary TB treatment (p=0.020)Conclusion: Gender influencing the treatment outcome of pulmonary TB patients in Surakarta. Further study covering more cases across all Community Health Center of Surakarta is required.